Barriers and Stimulus in Shared Decision Making Among Aesthetic Dermatologists in China: Findings from a Cross-Sectional Study - Fan J; Li S; Qiang Y; Duan Z; Wu A; Wang R (Dove Medical Press, 2024)
Jing Fan,1,2,* Shiyuan Li,3,* Yan Qiang,1,* Zhen Duan,3 Albert Wu,2 Ruiping Wang1- 3 1Clinical Research Center, Shanghai Skin Diseases Hospital, School of Medicine, Tongji University, Shanghai, People's Republic of China; 2Bloomberg School of Public Health, University of Johns Hopkins, Baltimore, MD, USA; 3School of Public Health, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Ruiping Wang, Email w19830901@126.comIntroduction: Shared decision making (SDM) is a collaborative process involving both healthcare providers and patients in making medical decisions, which gains increasing prominence in healthcare practice. But evidence on the level of SDM in medical practice and barriers as well as stimulus during the SDM implementation among aesthetic dermatologists is limited in China.Methods: From July to August 2023, 1938 dermatologists were recruited online in China. Data were collected through an electronic questionnaire covering: (1) demographic features; (2) SDM questionnaire physician version (SDM-Q-Doc); and (3) stimulus and barriers in SDM implementation. Logistic regression was applied to explore factors associated with SDM practice, barriers, and stimulus of SDM implementation, respectively.Results: The 1938 dermatologists included 1329 females (68.6%), with an average age of 35 years. The total SDM score ranged from 0 to 45, with a median value of 40 (IQR: 35- 44), and the median stimulus score and barriers scores were 28 (IQR: 24- 32) and 19 (IQR: 13- 26), respectively. The prevalence of good SDM was 27.2%, logistic regression indicated that female dermatologists (odds ratio, OR=1.21, 95% confidence interval, CI: 0.96- 1.51), and dermatologists with more years of aesthetic practice had a higher proportion of good SDM practice (OR was 1.44 for 5- 9 years, 1.58 for 10- 15 years and 1.77 for over 15 years). Moreover, female dermatologists and dermatologists with higher education level and serviced in private settings had lower barrier scores; female dermatologists and dermatologists with more years of aesthetic practice had higher stimulus scores.Conclusion: Chinese aesthetic dermatologists appear to implement SDM at an active level, with more stimulus and less barriers in SDM implementation. The integration of SDM into clinical practice among dermatologists is beneficial both for patients and dermatologists. Moreover, SDM practice should be strongly promoted and enhanced during medical aesthetics, especially among male dermatologists, dermatologists with less working experience, and those who work at public institutions.Keywords: shared decision making, dermatologist, good practice, barriers, stimulus